KADAR THIAMIN HIDROKLORIDA (VITAMIN B1) PADA NASI BERAS PUTIH DAN BERAS MERAH PADA BERBAGAI WAKTU PENYIMPANAN PADA ALAT MAGIC-COM - Mayun Laksmiwati, A. A. I. A.; Ratnayani, Ketut; Agustini, Ni Wayan (Jurnal Kimia (Journal of Chemistry), 2012)
This paper discusses the influence of storage time on the thiamine hydrochloride content in rice. White rice (C36) and red rice were stored in a magic-com for a period of time, of 0 hours, 6 hours and 12 hours. Thiamine hydrochloride contents in rice were separated with the use of a chromatography column with alumina oxide, while and the measurement was carried out by UV-Vis spectrophotometry. It was found that the thiamine hydrochloride content in red rice stored within 0 hours, 6 hours and 12 hours were, 5.3 mg/kg, 4.5 mg/kg and 2.8 mg/kg, respectively, while in white rice they were found to be 2.6 mg/kg, 2.0 mg/kg and 1.4 mg/kg, respectively.
Keywords: thiamine hydrocloride, red rice and white rice